Israel's Prophets and Israel's Past Essays on the relationship of prophetic texts and Israelite history in honor of John H. Hayes - Kelle, Brad E.; Megan Bishop Moore (New York T&T Clark International, 2006)
This volume is an inquiry into the complex relationship of the prophetic texts and Israelite history. Taken as a whole, the book provides a ""round-table"" discussion that examines the thesis that the study of prophetic literature (i.e., Isaiah, Jeremia
Keywords: Bible. -- Prophets -- Criticism, interpretation, etc. Bible. -- Old Testament -- History of Biblical events. Jews -- History -- To 70 A.D. RELIGION -- Biblical Studies -- Prophets. Bible. -- Old Testament. Bible. -- Prophets. History of Biblical events. Jews. Profeten (bijbelboeken) Bijbelse geschiedenis